2005
DOI: 10.1158/0008-5472.can-05-1460
|View full text |Cite
|
Sign up to set email alerts
|

The Role ofP53andMDM2Polymorphisms in the Risk of Esophageal Squamous Cell Carcinoma

Abstract: The tumor suppressor P53 pathway plays a crucial role in preventing carcinogenesis and genetic variations of this pathway may be associated with cancer susceptibility. We tested this hypothesis by examining the contribution of functional polymorphisms in P53 and MDM2 to risk of esophageal squamous cell carcinoma (ESCC). DNA from 758 ESCC patients and 1,420 controls were genotyped for P53 codon 72Arg>Pro and MDM2 309T>G polymorphisms. Odds ratios (OR) and 95% confidence intervals (CI) of ESCC were estimated by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
134
4
1

Year Published

2006
2006
2012
2012

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 170 publications
(151 citation statements)
references
References 38 publications
12
134
4
1
Order By: Relevance
“…20,21 In spite of the above discrepancy, we observed a similar association between P53 Arg72Pro and ESCC risk compared with Hong's and other previous studies (OR B2 for Pro/Pro genotype compared with Arg/Arg genotype, adjusted for age, sex, smoking or drinking status), though sample size, matching mode and study population were quite different from each other. [13][14][15][16] We confirm that P53 Arg72Pro polymorphism is a common susceptibility factor for ESCC in Chinese populations.…”
Section: Discussionsupporting
confidence: 58%
See 3 more Smart Citations
“…20,21 In spite of the above discrepancy, we observed a similar association between P53 Arg72Pro and ESCC risk compared with Hong's and other previous studies (OR B2 for Pro/Pro genotype compared with Arg/Arg genotype, adjusted for age, sex, smoking or drinking status), though sample size, matching mode and study population were quite different from each other. [13][14][15][16] We confirm that P53 Arg72Pro polymorphism is a common susceptibility factor for ESCC in Chinese populations.…”
Section: Discussionsupporting
confidence: 58%
“…Thus, all the participants were relatively homogeneous with regard to genetic background and environmental risk factors. Previous studies conducted in various tumour types in China showed that the GG genotype frequency ranged from 18 to 30% in controls, 16,[20][21][22][23][24] which indicated that genotype frequency varied in different populations even in the same country. Two of these studies also included MDM2 Del1518 and no association was observed between this polymorphism and cancer risk.…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…Several groups report that the G allele is associated with attenuation of the p53 pathway and enhanced early onset of, and increased risk for, tumorigenesis. [33][34][35][36] In contrast, several other groups have found no association between SNP309 and cancer risk or age of onset. [37][38][39][40] It is possible that the impact of this polymorphism may differ for different tumor types, or may depend upon the initiating molecular event that drives tumor cell development.…”
Section: Polymorphisms In Tp53: the Codon 47 Polymorphismmentioning
confidence: 99%